REPRESENTASI GENDER DALAM IKLAN PRODUGEN VERSI ‘TWO STORIES’ DI FACEBOOK FANPAGE - Elisabeth Intan Natalia; Rohmiati Rohmiati (Avant Garde, 2019)
This article aims to find out the gender representation existing in the advertisement of Produgen White coffee Two stories version. This type of research used is descriptive qualitative research with Semiotic Barthes. The focus of this research is on the exposure of denotation in which a man and woman appear to have different activities and behaviors. The man is described as the owner of a coffee shop business and a coffee enthusiast, while the woman is a yoga and healthy milk lover. All these moments have the meaning behind called connotationin in whise there are various gender stereotypes requiring men and women to act properly for social expectation, whereas in the concept of gender itself is the nature or behavior that can be exchanged, and is not a nature that must be met, is different from sex.